Retraction note: In vitro and in vivo evaluation of rotary-jet-spun poly(ɛ-caprolactone) with high loading of nano-hydroxyapatite (Journal of Materials Science: Materials in Medicine, (2019), 30, 2, (19), 10.1007/s10856-019-6222-1) - Andrade, Telmo M.; Mello, Daphne C. R. [UNESP]; Elias, Conceição M. V.; Abdala, Julia M. A.; Silva, Edmundo [UNESP]; Vasconcellos, Luana M. R. [UNESP]; Tim, Carla R.; Marciano, Fernanda R.; Lobo, Anderson O. (Springer Nature, 2025)
Retraction Note to: Journal of Materials Science: Materials in Medicine (2019) 30:19 The Editor-in-Chief has retracted this article. Image integrity concerns were raised regarding similarity between figure 3 in this article showing PCL/nHAp fibres and in figure 2 of another article by the same authors [1], showing PLA/TiO 2 fibres represented at differing scales. The authors were unable to provide the original images for evaluation. The Editor has therefore lost confidence in the underlying data of this article. Anderson O. Lobo disagrees with the retraction. Carla R. Tim agrees with this retraction. Telmo M. Andrade, Daphne C. R. Mello, Conceição M. V. Elias, Julia M. A. Abdala, Edmundo Silva, Luana M. R. Vasconcellos and Fernanda R. Marciano have not responded to correspondence regarding this retraction. The online version of the original article can be found under https://doi.org/10.1007/s10856-019-6222-1